1995
DOI: 10.2135/cropsci1995.0011183x003500040006x
|View full text |Cite
|
Sign up to set email alerts
|

Septoria tritici Resistance and Associations with Agronomic Traits in a Wheat Cross

Abstract: Septoria leaf blotch of wheat (Triticum aestivura L. em Thell) caused by the pathogen Septoria tri~'ci Rob. in Desm. [telemorph Mycosphaerella graminicola (Fuckel) J. Schroeter in Cohn] is a major disease reaching epidemic proportions in many parts of the world. Concerns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
4
18
0
1
Order By: Relevance
“…Levels of STB were substantially lower in later‐heading than in earlier‐heading lines (Fig. 1a), consistent with previous results (Shaner et al , 1975; Tavella, 1978; Eyal, 1981; van Beuningen & Kohli, 1990; Camacho‐Casas et al , 1995; Chartrain et al , 2004). Height components had a smaller effect on the variation of STB (Table 2), consistent with the results of Arama et al (1994, 1999), who studied a set of wheat cultivars.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Levels of STB were substantially lower in later‐heading than in earlier‐heading lines (Fig. 1a), consistent with previous results (Shaner et al , 1975; Tavella, 1978; Eyal, 1981; van Beuningen & Kohli, 1990; Camacho‐Casas et al , 1995; Chartrain et al , 2004). Height components had a smaller effect on the variation of STB (Table 2), consistent with the results of Arama et al (1994, 1999), who studied a set of wheat cultivars.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of individual major reduced‐height genes ( Rht ) on STB infection has been studied (Tavella, 1978; Eyal, 1981; Baltazar et al , 1990; van Beuningen & Kohli, 1990; Jlibene et al , 1992; Camacho‐Casas et al , 1995; Simón et al , 2004). Baltazar et al (1990) found that near‐isogenic lines carrying the Norin 10 gene Rht‐D1b (formerly Rht2 ) were less susceptible to STB than lines with no Rht genes, or with the other Norin 10 gene Rht‐B1b (formerly Rht1 ), although the Rht‐D1b line was shorter than the other two.…”
Section: Introductionmentioning
confidence: 99%
“…However, several European lines had better resistance than Cappelle Desprez, which suggests that resistance genes must have been accumulated from several sources. Quantitative resistance to septoria tritici blotch in European wheat cultivars is therefore probably polygenic, controlled by many genes, each with a small effect, as is similar resistance in American material (Jlibene et al ., 1994; Camacho‐Casas et al ., 1995). Progress in improving resistance to septoria tritici blotch may be made by intercrossing lines from different European breeding programmes.…”
Section: Discussionmentioning
confidence: 99%
“…In highly susceptible cultivars, this disease may reduce grain yield by 50% (Eyal and Ziv, 1974). Regarded as a wet weather disease (Shaner and Finney, 1976), it is highly destructive in a number of European countries, western Australia (Eyal et al, 1973), New Zealand (Gaunt et al, 1986), the Southern Cone of Latin America (De Ackermann et al, 1995), the Pacific Northwest (Camacho‐Casas et al, 1995), and eastern regions of the USA (Shaner and Finney, 1982). In the northern Great Plains of the USA, severe epidemics of septoria diseases on winter wheat have been observed during the last decade when S. tritici was the predominant causal species.…”
mentioning
confidence: 99%
“…Wilson (1985) proposed three different genes conferring resistance to STB, designated Slb1 , Slb2 , and Slb3 A second inheritance model proposes that resistance is conditioned by more than one major gene (Eyal et al, 1987). Resistance to STB also has been considered as a quantitative trait, as intermediate resistance has been commonly identified in wheat and a continuous distribution of phenotypes in the F 2 population for disease reaction was observed in the field (Camacho‐Casas et al, 1995). Jlibene et al (1994) and Simon and Cordo (1998) reported significant GCA for resistance to STB.…”
mentioning
confidence: 99%